PREDICTION OF THE SPECTRUM FOR EXCITATION OF THE VANDERWAALS MODES IN ARHCN - Clary, D; Dateo, C; Stoecklin, T (1990)
A calculation of the spectrum for the excitation of the van der Waals modes in ArHCN is reported. The coupled electron pair approximation is used to compute an ab initio potential energy surface for the interaction of Ar with rigid HCN. The rovibrational bound states for the complex are calculated using a variational coupled-basis set method in which a self-consistent field approach is used to optimize simultaneously the basis sets for both the intermolecular bending and stretching motions in the van der Waals molecule. The calculations are compared with experimental results, including a measurement of the infrared spectrum of ArHCN in the region of the CH stretching vibration. The calculations predict that several bending modes with frequencies less than 20 cm -1 should have excitation intensities large enough to be observed. These low frequency bending modes arise from the small rotational constant of the HCN molecule and are not due to special features of the Ar-HCN potential energy surface. © 1990 American Institute of Physics.